FOSTERING INDIVIDUAL CREATIVITY AMONG ACADEMICIANS: AN INTEGRATED CONCEPTUAL MODEL - Rozain, Muhammad Farhan; Munir, Rosintansafinas (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
In higher education institutions, creativity represents a high-level capability that has become essential for managing the rapid pace of digital transformation, increasing performance expectations, and ongoing advancements in teaching and learning methodologies. Indeed, efforts to enhance creativity increasingly rely on workplace interactions that play a significant role in shaping employee creative performance. Accordingly, this conceptual framework enriches the understanding of individual creativity among academicians by examining four key antecedents: work engagement, perceived visionary leadership, digital platform capability, and training. This study, grounded in Amabile’s Componential Theory of Creativity posits that organizational and environmental conditions that enable and encourage creative expression significantly influence the creative output of academicians. This study uses a quantitative research design to examine the antecedents that influence the creativity among academicians at the Faculty of Accountancy, Universiti Teknologi MARA (UiTM). A survey of academicians will be conducted to examine the factors influencing individual creativity. This paper proposes an integrated model that provides theoretical clarity and practical guidance for higher education institutions, particularly faculty of accountancy, in their efforts to cultivate a creative academician. Further, this study provides guidelines and strategic actions aimed at enhancing academicians’ creativity to drive teaching innovation, improve instructional quality, and strengthen institutional competitiveness, while also providing a foundation for future empirical research.